Clinical and diagnostic aspects of abnormal uterine bleeding in reproductive aged women with extragenital pathology - I.A. Tuchkina; L.A. Vygivska; E.V. Blagoveshchensky; R.E. Blagoveshchensky (Publishing House TRILIST, 2021)
Study objective: to determine the clinical and diagnostic features of the abnormal uterine bleeding (AUB) in women of reproductive age with extragenital pathology. Materials and methods. The study involved a retrospective assessment of 400 case histories of reproductive aged women with AUB who underwent inpatient treatment. The main clinical group (I) consisted of 300 case histories of women with AUB and concomitant extragenital disorders, control group (II) consisted of 100 case histories of somatically healthy women with AUB. An ultrasound scan with Doppler mapping was performed to assess the pelvic organs. All women underwent hysteroscopy and/or separate diagnostic curettage with further morphological assessment of the endometrium. Results. The most common extragenital disorder was diseases of the circulatory system and endocrine system, diseases of the digestive system. 123 patients (41%) had concomitant hypertension and obesity, 76 (25.3%) - obesity and varicose veins, 53 (17.6%) - somatoform autonomic dysfunction and chronic gastritis, 39 (13%) - obesity and diabetes mellitus, 24 (8%) - chronic gastritis and obesity. AUB was complicated by anemia of varying severity in 176 (58.6%) women. According to ultrasound data the most common endometrial disorder in women of group I was glandular hyperplasia of the endometrium. Conclusion. A retrospective analysis of case histories showed a high prevalence of AUB among women with extragenital pathology, which is a clinical indicator of major menstrual disorders in this category of patients and can be a serious problem for women's health in general. The need to study the prevalence and identify the main risk factors for the AUB development will make it possible to provide a general strategy for its prevention, improve the reproductive potential of women and avoid serious abnormal changes in the process of fulfilment of the reproductive function in young women.